Discovery of substituted 1, 4-dihydroquinolines as novel promising class of P-glycoprotein inhibitors: First structure–activity relationships and bioanalytical studies. Issue 15 (1st August 2015) - Hemmer, Marc; Krawczyk, Sören; Simon, Ina; Hilgeroth, Andreas
Graphical abstract: Abstract: Multidrug resistance (mdr) is the most important problem in the therapeutical treatment of cancer. One central problem in the resistance proceeding is the expression of transmembrane efflux pumps which transport drugs out of the cells. We developed novel substituted 1, 4-dihydroquinolines as inhibitors of the transmembrane efflux pump P-glycoprotein. Structure–activity relationships are discussed for this first series. Promising active inhibitors have been identified and first bioanalytical studies have been carried out to address questions of cellular toxicity, P-gp substrate as well as mdr reversal properties.